2007
DOI: 10.1161/circresaha.107.157552
|View full text |Cite
|
Sign up to set email alerts
|

Modest Reductions of Cardiac Calsequestrin Increase Sarcoplasmic Reticulum Ca 2+ Leak Independent of Luminal Ca 2+ and Trigger Ventricular Arrhythmias in Mice

Abstract: Abstract-Cardiac calsequestrin-null mice (Casq2 Ϫ/Ϫ ) display catecholaminergic ventricular tachycardia akin to humans with CASQ2 mutations. However, the specific contribution of Casq2 deficiency to the arrhythmia phenotype is difficult to assess because Casq2 Ϫ/Ϫ mice also show significant reductions in the sarcoplasmic reticulum (SR) proteins junctin and triadin-1 and increased SR volume. Furthermore, it remains unknown whether Casq2 regulates SR Ca 2ϩ release directly or indirectly by buffering SR luminal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 30 publications
5
102
2
Order By: Relevance
“…Each molecule of CSQ2 can bind 18 -50 Ca 2ϩ ions. CSQ2 is also believed to regulate the activity of RyR2 Ca 2ϩ release channels by controlling the local luminal Ca 2ϩ concentration in the vicinity of the RyR2 channels (11)(12)(13).…”
Section: Camentioning
confidence: 99%
“…Each molecule of CSQ2 can bind 18 -50 Ca 2ϩ ions. CSQ2 is also believed to regulate the activity of RyR2 Ca 2ϩ release channels by controlling the local luminal Ca 2ϩ concentration in the vicinity of the RyR2 channels (11)(12)(13).…”
Section: Camentioning
confidence: 99%
“…Phospholamban (PLB) inhibits SERCA2a activity, but phosphorylation on either serine 16 (S 16 ) or threonine 17 (T 17 ) relieves this inhibition. Calsequestrin 2 (CSQ2) may be uniquely important for calcium signaling because it is the principal calcium storage protein in the SER and, as part of a protein complex with the ryanodine receptor 2, helps to control the amount of calcium released for contraction (7).…”
mentioning
confidence: 99%
“…CASQ2 null mice, when adrenergically stressed, show enhanced fractional SR Ca 2ϩ release, Ca 2ϩ leak, and arrhythmias (17). Similarly, loss of TRD1 increases susceptibility to triggered arrhythmia (2). These knockout mouse models have shown that the integrity of the triadic protein complex is critical to the proper modulation of RyR2 activity.…”
Section: Discussionmentioning
confidence: 99%